Diversity of Welfare Systems in the EU: A Challenge for Policy Coordination - Gudrun Biffl (Austrian Institute of Economic Research (WIFO), 2003)
As the EU economies and societies become increasingly integrated, and as labour market behaviour patterns converge across borders, the EU strives to develop a substantially common social identity. To this end, it seeks to promote the development of a sustainable institutional framework which facilitates flexibility and structural change in the economy and the labour market, while at the same time providing a meaningful social safety net ("flexicurity"). However, it would be unrealistic to try to establish a common EU social protection model under the prevailing great differences in social organisation of the various EU countries. The more immediate object for the EU should be to identify the mechanism by which social protection is ensured, what developments jeopardise the continued universal coverage of all members of society, what factors are responsible for the socio-economic exclusion of groups of people, why these differ by model of social organisation, and last but not least, what the gaps are in the statistical data which prevent a proper evaluation of economic wellbeing under the different welfare models. The thrust of this paper is that the wellbeing of every society depends upon the interaction of the market, the household/family and the state. The exclusion of the household sector from the regular statistical framework - and orthodox economic theory - ignores the fact that the various models of social organisation give different relative weights to - and impose different roles on - the three pillars of social organisation. A different set of taxes, transfer payments and public services in the various welfare models in the EU results in a divergence of incentives to the private sector and/or the household to provide social services, in particular care work. This results in a different degree of integration of the working age population into the labour force, the quality of work and the price and quality of social protection. Models which allow targeting for individual needs are best able to cope with the current trends of increasing fragmentation and diversity of social functions.
Keywords: 330; Soziale Sicherheit; Länderbericht; EU-Staaten